Bolus-tracking arterial spin labeling : a new approach to quantifying cerebral perfusion with magnetic resonance imaging - Kelly, Michael (TCIN (Trinity College Institute of Neuroscience) Scholarly Publications, 2009)
The body of work presented herein describes the development a new technique for the quantification of cerebral perfusion, termed bolus-tracking arterial spin labeling (btASL). The technique uses a novel non-compartmental model of cerebral perfusion in combination with ASL magnetic resonance imaging (MRI) experiments to quantify the changes in the perfusion state of the rat brain under the following conditions: increased neural activity, normal ageing and methylenedioxymethamphetamine (MDMA) administration.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin